Women and Social Security in Retirement: A Comparative Analysis - Sandra Hutton; Peter Whiteford (Luxembourg Income Study (LIS), 1992)
A comparative study concerning the circumstances of women in four European countries, utilizing both theoretical literature concerned with welfare states, and empirical literature based on LIS data. Both cross country and gender comparisons are analyzed.
Keywords: 330